THE NEED FOR IMPLEMENTATION OF ASPECT ANALYSIS CHARACTER IMAGES IN POLYCULTURAL EDUCATION OF STUDENTS - L. Udovichenko (Academy of Cognitive and Natural Sciences, 2004)
The article deals with some problems concearning the necessity to use the national aspect of characters in prose works in the process of their studying in high-school classes. The contents of this kind of activities are given scientific grounds.